RANS simulations of transitional flow by γ model. Issue 10 (26th November 2019) - de Rosa, D.; Catalano, P.
ABSTRACT: Turbulence models are widely accepted in CFD codes in order to close Reynolds Averaged Navier Stokes equations. In the years more and more complex models were proposed to improve the reliability of numerical results, however, these models neglect laminar and transition regions in the framework of a 'fully turbulent' assumption. Techniques to compute both laminar and turbulent zones were proposed, fixing a transition location. The requirement is to know transition point a priori from experimental data or using other transition prediction approaches as e N method. Nevertheless, the transition region is not computed and a sudden shift between laminar and turbulent region is observed. In the last decades, several methods to model transition region in CFD codes have been investigated and proposed. Following the last developments, the authors implemented the Menter's γ transition model into an in-house developed flow solver and the present study aims to assess the newly introduced transition prediction capabilities on 2D and 3D incompressible flows.